2006
DOI: 10.1002/eji.200636190
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral B cell receptor editing may promote the production of high‐affinity autoantibodies in CD22‐deficient mice

Abstract: CD22-deficient mice are characterized by B cell hyperactivity and autoimmunity. We have constructed knock-in CD22 -/-mice, expressing an anti-DNA heavy (H) chain (D42), alone or combined with Vj1-Jj1 or Vj8-Jj5 light (L) chains. The Ig-targeted mice produced a lupus-like serology that was age-and sex-dependent. High-affinity IgG autoantibodies were largely dependent on the selection of B cells with a particular H/L combination, in which a non-transgenic, endogenous L chain was assembled by secondary rearrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Whether receptor editing in transitional B cells normally occurs is uncertain. Although receptor editing in mature and germinal center B cells is well documented, these studies were conducted under special circumstances, such as immunization, ongoing autoimmune responses, or in cells with mutant BCR signaling molecules (11)(12)(13)(14)(15). This type of peripheral receptor editing, also known as "receptor revision", is purported to generate high-affinity Abs rather than to silence autoreactive B cell clones.…”
Section: B Cell Development In Bone Marrow (Bm)mentioning
confidence: 99%
“…Whether receptor editing in transitional B cells normally occurs is uncertain. Although receptor editing in mature and germinal center B cells is well documented, these studies were conducted under special circumstances, such as immunization, ongoing autoimmune responses, or in cells with mutant BCR signaling molecules (11)(12)(13)(14)(15). This type of peripheral receptor editing, also known as "receptor revision", is purported to generate high-affinity Abs rather than to silence autoreactive B cell clones.…”
Section: B Cell Development In Bone Marrow (Bm)mentioning
confidence: 99%
“…Studies in BCR Tg models have demonstrated that B cells with strong self-reactivity are censored in the bone marrow largely through receptor editing and deletion (1)(2)(3)(4)(5). Elegant work by several investigators has shown that secondary rearrangement at the L chain (LC) locus is a particularly effective mechanism that B cells commonly use to veto self-reactivity (6 -9).…”
mentioning
confidence: 99%
“…Engagement of SHIP via FcγRII is known to inhibit B-cell proliferation, Akt activation, and survival [37][38][39] Even in mice bearing an anti-DNA transgene and deregulation of BCR signaling by CD22 mutation show a sex bias in development of autoimmunity [43], suggesting additional sex-dependant factors contribute beyond initial B-cell dysfunction. The mechanisms contributing to female bias in autoantibody-mediated diseases are not completely understood but may involve mechanisms related to sex hormones since some studies find blocking sex hormone signaling in autoimmune female mice led to amelioration of disease [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, another contributing factor might be that mutation of TAPP1-and TAPP2-binding sites for PI(3,4)P2 increases that amount of this PI available for recruiting Akt to the plasma membrane, where it can be phosphorylated and activated by PDK1. It should be noted that while PI(3,4)P2 has been implicated in Akt phosphorylation and activation, other studies suggest that PIP3 is the limiting factor for Akt membrane recruitment and activation [20,22,32].Engagement of SHIP via FcγRII is known to inhibit B-cell proliferation, Akt activation, and survival [37][38][39] Even in mice bearing an anti-DNA transgene and deregulation of BCR signaling by CD22 mutation show a sex bias in development of autoimmunity [43], suggesting additional sex-dependant factors contribute beyond initial B-cell dysfunction. The mechanisms contributing to female bias in autoantibody-mediated diseases are not completely understood but may involve mechanisms related to sex hormones since some studies find blocking sex hormone signaling in autoimmune female mice led to amelioration of disease [44,45].…”
mentioning
confidence: 99%